ANALYSIS OF LANGUAGE STYLE IN THE NOVEL “ORANG ORANG BIASA” BY ANDREA HIRATA AS LITERATURE TEACHING MATERIAL IN SENIOR HIGH SCHOOL - Muzdalifah, Muzdalifah; Efendi, Irfan; Fajri, Khoirul (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This study aims to delineate the language styles present in Andrea Hirata's novel "Orang-Orang Biasa" and ascertain its applicability as teaching material for historical story texts in Indonesian language learning. Employing a descriptive qualitative method, the research analyzes the novel to discern the form and meaning of language styles within it. The data source is the novel itself, and data collection involves library research, reading techniques, and note-taking. The note technique records the analysis results of the novel. The research unfolds in three stages: planning, implementation, and data reporting. The novel exhibits various language styles, categorized as: 1) comparison styles, encompassing simile, personification, metaphor, pleonasm, periphrasis, antithesis, prolepsis; 2) opposition styles, including hyperbole, irony, litotes, oxymoron, zeugma, innuendo, satire, paradox, climax, anticlimax, hypocrisy, cynicism, and sarcasm; 3) linking styles, consisting of metonymy, synecdoche, euphemism, allusion, eponymy, epithet, antonomasia, ellipsis, asyndeton, and polysyndeton; and 4) repetition styles, such as alliteration, assonance, chiasmus, epizeuxis, anaphora, epistrophe, mesodiplosis, epanalepsis, and anadiplosis. These language styles contribute to the novel's aesthetic appeal, imparting an artistic and dramatic essence. The findings are applicable to Indonesian language learning in SMA class XII semester 2, particularly in historical story text materials covering language styles within basic competency 3.4 (analyzing the language of historical stories or novels) and basic competency 4.4 (writing personal historical stories with attention to language). The teaching materials developed for this study utilize a modular approach.